Risk Factors for Postoperative Cognitive Dysfunctions in Elderly Patients - N. Yu. Ibragimov; K. M. Lebedinsky; B. Ye. Mikirtumov; V. Ya. Gelman; S. V. Obolensky; V. S. Kazarin (Общая реаниматология, 2008)
Objective: to study the impact of a wide spectrum of factors on the development of postoperative delirium in elderly patients in relation to the changes in their cognitive functions depending on the type of anesthesia and period after surgery. Subjects and methods. The study covered 100 patients aged 65—90 years who had been electively operated on under general, regional, and combined anesthesia. Their cognitive status was elevated before and 1, 4, and 7 days after surgery, by using the Mini-Mental State Examination (MMSE) schedule. The diagnosis was postoperatively established on the basis of interviews, by applying the diagnostic criteria of ICD-10 and DSM-IV (American Psychiatric Association, 1994) and verified by a psychiatrist’s consultation. Results. Seventeen patients developed delirium within the first two days following surgery. Elevated plasma sodium (p<0.000001), leukocytosis (p<0.00002), and postoperative analgesia mode (p<0.02) proved to be statistically significant risk factors for delirium. Worse results of MMSE tests at all postoperative stages than those obtained prior to surgery were significant (p<0.05). Comparing the results obtained on days 1, 4, and 7 showed a significant cognitive improvement. Analysis indicated no significant differences in MMSE changes between the groups of general, regional, and combined anesthesia at all study stages. Conclusion. In elderly patients, surgery and anesthesia lead to a considerable deterioration of cognitive functions even if the development of delirium can be avoided. There is a significant correlation of the development of delirium with leukocytosis, hypernatremia, and postoperative analgesia mode. Key words: anesthesia, postoperative delirium, cognitive status, MMSE, elderly age.